RELACIONES RECIPROCAS EN EL MODELO DE TRIPLE HÉLICE MEDIANTE VARIABLES DE INTERACCIÓN - Sapién-Aguilar, Alma Lilia; Piñón-Howlet, Laura Cristina; Gutiérrez-Diez, María Del Carmen (European Scientific Journal, ESJ, 2015)
The Triple Helix Model (THM) postulates that universitygovernment- industry is the key to innovation processes in any society. The objective of this study was to analyze the reciprocal relations in the THM by interaction variables. Three interaction variables were considered: 1) between the public and the academic sector; 2) involving the academic sector and industry and; 3) among the industry and public sector. For the first interaction it was evaluated the approach and matching, for the second the management and entailment and for the third interaction the collaboration and cooperation. The study was conducted in the period from 2013 to 2014 through theoretical investigations, using the technique of documentary analysis and historical-logical method. The research was descriptive, using a field design, non-experimental, cross-sectional descriptive. The results showed that THM might be used as a driver of innovation not only for the market but also to improve some social problems. In conclusion, the convergence known as THM is the key for improving innovation processes in any society.